On the reliability of residual stress measurements in polycarbonate samples by the hole drilling method. (October 2018) - Magnier, A.; Scholtes, B.; Niendorf, T.
Abstract: The present study introduces a procedure to analyze residual stresses in polymer materials using the hole drilling method. This method is widely applied in metallic materials, however its application in polymer materials is not straightforward. In previous work [1, 2], the experimental set-up was improved to gain reproducible results, however, in-depth analysis of the reliability of measurements was not conducted. In order to gain appropriate information, a known loading stress was introduced in bending samples made of polycarbonate. By measuring the total stresses in the samples and comparing them with theoretical expectations, it is shown that the hole drilling method delivers reliable results and has a high potential for residual stress analysis in a variety of polymer materials. Based on this approach, it is shown that the resistance to environmental stress cracking of polycarbonate can be significantly improved by introducing compressive residual stress states. Highlights: Residual stresses in polycarbonate samples are measured with the hole drilling method. By inducing a defined load in materials, the reliability of residual stress measurements is investigated. Two heat treatments are used to induce different residual stress states in polycarbonate materials. The influence of residual stresses in polycarbonate samples on environmental stress corrosion is demonstrated. Compressive residual stresses increase the resistance to environmental stress corrosion.